Genetic diversity of Arcobacter isolated from bivalves of Adriatic and their interactions with Mytilus galloprovincialis hemocytes - Ottaviani, Donatella (Microbiologyopen, 2016)
The human food‐borne pathogens Arcobacter butzleri and A. cryaerophilus have been frequently isolated from the intestinal tracts and fecal samples of different farm animals and, after excretion, these microorganisms can contaminate the environment, including the aquatic one. In this regard, A. butzleri and A. cryaerophilus have been detected in seawater and bivalves of coastal areas which are affected by fecal contamination. The capability of bivalve hemocytes to interact with bacteria has been proposed as the main factor inversely conditioning their persistence in the bivalve. In this study, 12 strains of Arcobacter spp. were isolated between January and May 2013 from bivalves of Central Adriatic Sea of Italy in order to examine their genetic diversity as well as in vitro interactions with bivalve components of the immune response, such as hemocytes. Of these, seven isolates were A. butzleri and five A. cryaerophilus, and were genetically different. All strains showed ability to induce spreading and respiratory burst of Mytilus galloprovincialis hemocytes. Overall, our data demonstrate the high genetic diversity of these microorganisms circulating in the marine study area. Moreover, the Arcobacter–bivalve interaction suggests that they do not have a potential to persist in the tissues of M. galloprovincialis.